2021
DOI: 10.48550/arxiv.2105.10617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shocked Molecular Hydrogen and Broad CO lines from the Interacting Supernova Remnant HB 3

J. Rho,
T. H. Jarrett,
L. N. Tram
et al.

Abstract: We present the detections of shocked molecular hydrogen (H 2 ) gas in near-and mid-infrared and broad CO in millimeter from the mixed-morphology supernova remnant (SNR) HB 3 (G132.7+1.3) using Palomar WIRC, the Spitzer GLIMPSE360 and WISE surveys, and HHSMT. Our near-infrared narrow-band filter H 2 2.12 µm images of HB 3 show that both Spitzer IRAC and WISE 4.6µm emission originates from shocked H 2 gas. The morphology of H 2 exhibits thin filamentary structures and a large scale of interaction sites between t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…G132.7+01.3 has been studied in γ-rays, X-rays, radio, infrared and mm wavelengths (e.g. Routledge et al 1991;Fesen et al 1995;Lazendic & Slane 2006;Zhou et al 2016;Rho et al 2021, see also Introduction). Here we present the main results and conclusions regarding the properties and evolution of HB3 as extracted by the comparison of its emission properties in different electromagnetic bands.…”
Section: Comparison With Other Wavelengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…G132.7+01.3 has been studied in γ-rays, X-rays, radio, infrared and mm wavelengths (e.g. Routledge et al 1991;Fesen et al 1995;Lazendic & Slane 2006;Zhou et al 2016;Rho et al 2021, see also Introduction). Here we present the main results and conclusions regarding the properties and evolution of HB3 as extracted by the comparison of its emission properties in different electromagnetic bands.…”
Section: Comparison With Other Wavelengthsmentioning
confidence: 99%
“…This evidence was verified by multimeter observations of CO lines, conducted by Zhou et al (2016) which revealed a substantial amount of molecular gas around −43 km s −1 , being morphologically and dynamically correlated with HB3. Finally, shocked molecular hydrogen (H 2 ) and broad CO was recently detected in the near/mid infrared and millimeter bands, respectively, whose morphological and kinematic properties provide an additional evidence on the interaction of the SNR with the surrounding clouds (Rho et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We follow the same roadmap for prediction of CO line profile with IC443. Excition models were used to estimate shock properties in both observations of van Dishoeck et al (1993) and Rho et al (2021). Reach et al (2019) has developed theoretical line profile prediction for H 2 from various observation of IC443 B, C and G, which will served as useful shock diagnostic.…”
Section: Line Profile Fits For Ic443mentioning
confidence: 99%
“…SNR-MC interactions have been intensively studied by observations of the shocked regions by using both molecular and atomic gas tracers (see e.g., Wootten 1977;Denoyer 1979a,b;Wootten 1981;Denoyer 1983;Tatematsu et al 1985Tatematsu et al , 1987Fukui & Tatematsu 1988;Tatematsu et al 1990a,b;White et al 1987;van Dishoeck et al 1993;White 1994;Koo & Moon 1997a,b;Seta et al 1998Seta et al , 2004Wilner et al 1998;Arikawa et al 1999;Reach & Rho 1999Reach et al 2002Reach et al , 2005aNeufeld et al 2007;Yuan & Neufeld 2011;Gusdorf et al 2012;Anderl et al 2014;Reach et al 2019;Dell'Ova et al 2020;Rho et al 2021). Commonly, the rovibrational lines of H 2 and CO are notably used to characterize the SNR shocks.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to a dipole moment, CO complements H 2 by probing the cooler and denser part in the shocked regions. Both the excitation diagram ("Boltzmann plot"), relation between the column density of the rotationally excited levels and their energy above the ground state , e.g., Neufeld et al 2007;Yuan & Neufeld 2011), and the resolved velocity profiles (e.g., Reach et al 2019;Rho et al 2021) have been used to constrain the physical properties of the shocked gas.…”
Section: Introductionmentioning
confidence: 99%